A method for the preparation of rhodium-ruthenium binary metal oxides for use in the anode of a pem electrolyser
Patent Information
- Application Number
- CN202410247317.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-05
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-03-05
AI Technical Summary
PEM-WE anodes exhibit poor stability under conditions of strong acidity, high oxidation voltage, and high oxygen concentration. Ru-based materials are prone to over-oxidation at OER potential, leading to decreased stability of Ru-based electrode materials and limiting the large-scale application of PEM-WE technology.
Ruthenium-based binary metal oxide nanoparticles with controllable size were prepared by impregnation reduction method. Rh and Ru were introduced to form a binary metal oxide. Carbon black was used to bind the element precursor, the electronic structure of Ru species was optimized, and unstable substances were removed by acid washing to form RhRu3Ox nanoparticles.
RhRu3Ox nanoparticles exhibit high activity and stability in the PEM-WE system, reducing hydrogen production costs to only one-seventh of those of Ir-based materials, making them suitable for large-scale production. Their energy consumption is 43.2 kWh/kg H2-1, significantly lower than that of Ir-based materials.
Smart Images

Figure CN118026300B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nano-metal oxide material preparation, and relates to a method for preparing rhodium-ruthenium binary metal oxide for PEM electrolytic cell anodes. Background Technology
[0002] Breaking free from dependence on fossil fuels and directly utilizing renewable energy to drive material conversion, thereby achieving an efficient and clean energy utilization system, is the ultimate vision for humankind's sustainable development. As the world's largest renewable energy power producer, my country alone generates over 100 billion kilowatt-hours of curtailed renewable energy annually from wind, solar, and hydropower plants. With the continuous decline in the cost of renewable electricity, utilizing these inexpensive, abundant, and "green" electrons to electrochemically synthesize basic chemical / fuel feedstocks is not only environmentally friendly but also economically attractive. However, the fluctuating nature of renewable energy generation has hindered its effective utilization by industry.
[0003] Fortunately, PEM-WE technology, as a technology applicable to intermittent power generation, can be well integrated with renewable energy power generation devices. It uses renewable electricity to decompose water into hydrogen and oxygen, thus converting excess electrical energy into chemical energy. Compared to traditional alkaline water electrolysis technology, PEM-WE technology offers higher current density, higher hydrogen purity, and faster response speed. For these reasons, PEM-WE technology is gradually becoming the mainstream technology for hydrogen production through water electrolysis.
[0004] However, the extremely harsh operating conditions of PEM-WE anodes—high acidity, high oxidation voltage, and high oxygen concentration—are the primary reason limiting the application of PEM-WE technology. Iridium (Ir)-based materials are currently the only catalysts capable of meeting the stability requirements of commercial PEM-WE equipment. However, due to the extremely limited reserves of Ir in the Earth's crust (0.02-0.10 ng),... Ir The high cost of Ru (with a per-g ratio) and its expensive price limit the large-scale application of PEM-WE technology, preventing further reductions in hydrogen production costs. Therefore, the potential application of Ru-based materials (costing one-seventh that of Ir-based materials) in PEM-WE devices has attracted attention. However, the Boehringer Indices (BOI) of RuO2 show that at the OER potential, Ru species inevitably undergo peroxidation, forming volatile RuO4 and RuO5. 2- This leads to a decrease in the stability of Ru-based electrode materials. Summary of the Invention
[0005] Based on the problems existing in the prior art, the present invention provides a method for preparing a rhodium-ruthenium binary metal oxide for PEM electrolyzer anodes. The aim is to stabilize the alloy oxide lattice through fine structure-property design, maximize the OER performance of Ru-based electrode materials while maintaining their stability, and ultimately use them as PEM-WE anodes for commercial hydrogen production.
[0006] To achieve its objectives, the present invention employs the following technical solution:
[0007] This invention relates to a method for preparing rhodium-ruthenium binary metal oxides for PEM electrolytic cell anodes. Ruthenium-based binary alloy oxide nanoparticles with controllable size and no inter-element phase separation are constructed from the bottom up using an impregnation reduction method. The binding effect of carbon black, a structural aid, prevents excessive Ostwald ripening of the elemental precursors during the high-temperature reduction step, allowing the nanoparticles to maintain a uniform and small size. Smaller particle size means a larger exposed specific surface area per unit mass, thereby significantly improving the utilization efficiency of the precious metal. Furthermore, the introduction of the electronic aid Rh to form a binary metal oxide with Ru optimizes the electronic structure of Ru species while stabilizing the crystal lattice of the nanoparticles. Finally, acid washing removes unstable substances from the surface, ensuring that the final product maintains lattice stability while exhibiting high activity. This invention, starting from microstructure design, provides a new approach to improving the stability of Ru-based electrode materials and ultimately applying them to the anodes of PEM-WE equipment.
[0008] The method for preparing the rhodium-ruthenium binary metal oxide for the anode of a PEM electrolytic cell according to the present invention specifically includes the following steps:
[0009] a. Add RhCl3 to hydrochloric acid and dissolve until transparent. Then add deionized water and RuCl3. After ultrasonic treatment of the resulting mixture, add carbon black and stir until evenly dispersed. Dry and collect the powder sample.
[0010] b. The dried powder was placed in an H2 / Ar atmosphere for reduction to obtain a ruthenium-rhodium alloy RhRu3 / C supported on a carbon support;
[0011] c. Anneal the RhRu3 / C sample in air to oxidize the carbon support into CO2 and remove it, thus obtaining a supportless ruthenium-rhodium binary metal oxide.
[0012] d. The carrier-free ruthenium-rhodium binary metal oxide sample is acid-washed in HCl solution, then washed with deionized water and dried to obtain RhRu3O for use as the anode in a PEM electrolytic cell. x catalyst.
[0013] Furthermore, in step a, the molar ratio of RhCl3 to RuCl3 is 1:3.
[0014] Furthermore, in step a, the weight of carbon black is 2-6 times the total metal weight in RhCl3 and RuCl3.
[0015] Further, in step a, the drying is performed using a rotary evaporator at 50-90°C and 6-9 × 10⁻⁶ °C. 3 Drying is carried out at Pa.
[0016] Furthermore, in step b, the reduction is carried out at 800-1000°C for 1.5-3 hours.
[0017] Furthermore, in step c, the annealing temperature is 350-550℃ and the annealing time is 2-4 hours.
[0018] Further, in step d, the concentration of the HCl solution is 0.5-2M, the ratio of sample to HCl solution is 30-60mg:10-30mL, and the acid washing time is 10-15h.
[0019] Compared with existing technologies, the beneficial effects of this invention are reflected in:
[0020] The PEM-WE anode catalyst used in this invention is RhRu3O x Nanoparticles, synthesized using a highly stable method, are easy to mass-produce, and are priced at only one-seventh of the currently only commercially available Ir-based material, possessing immense commercial value. Using RhRu3O x Nanoparticles, used as an anode catalyst, showed an energy consumption of only 43.2 kWh / kg in the PEM-WE system. H2 -1 The cost of hydrogen production is 2.3 yuan per standard cubic meter, which is significantly lower than the price of about 5 yuan per standard cubic meter for industrial water electrolysis. Attached Figure Description
[0021] Figure 1 This is the intended synthesis process of the present invention.
[0022] Figure 2 The images show transmission electron microscopy (TEM) images (a and b correspond to different magnifications) and high-angle annular dark-field scanning transmission (HAADF-STEM) images (c and d correspond to different magnifications) of the RhRu3 / C nanoparticles prepared in this invention.
[0023] Figure 3 RhRu3O prepared for this invention x Transmission electron microscopy (TEM) images of nanoparticles (a and b correspond to different magnifications) and high-angle annular dark-field scanning transmission (HAADF-STEM) images (c and d correspond to different magnifications).
[0024] Figure 4 RhRu3O prepared for this invention x The elemental distribution maps of the nanoparticles obtained by scanning transmission electron microscopy (STEMmapping) show that a to d correspond to the high-angle annular dark field image (a), ruthenium elemental distribution (b), rhodium elemental distribution (c), and oxygen elemental distribution (d), respectively.
[0025] Figure 5 RhRu3O prepared for this invention x X-ray diffraction (XRD) patterns of nanoparticles and control samples.
[0026] Figure 6 RhRu3O prepared for this invention x Linear sweep voltammetry (LSV) curves of binary metal oxides formed by nanoparticles and other platinum group elements with Ru in 0.1 M HClO4.
[0027] Figure 7 RhRu3O prepared for this invention x X-ray photoelectron spectroscopy (XPS) spectra of nanoparticles and control samples in the 3d orbital of Ru.
[0028] Figure 8 To improve the RhRu3O prepared in this invention x A schematic diagram of the PEM-WE device used for actual production evaluation of nanoparticles.
[0029] Figure 9 RhRu3O prepared for this invention x Activity test diagrams of nanoparticles and control samples in PEM-WE devices at room temperature.
[0030] Figure 10 RhRu3O prepared for this invention x Stability test results of nanoparticles in PEM-WE devices at room temperature. Detailed Implementation
[0031] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to examples. The following content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, as long as they do not depart from the inventive concept or exceed the scope defined by the claims, all of which should fall within the protection scope of the present invention.
[0032] Example 1
[0033] like Figure 1 As shown, in this embodiment, RhRu3O, used as an anode catalyst for a PEM electrolyzer, was prepared according to the following steps. x Nanoparticles:
[0034] a. Add 0.2 mmol RhCl3 to 20 mL of HCl solution (mass concentration 36.0–38.0%) and dissolve until transparent. Then add 130 mL of deionized water (DIW) and 0.6 mmol RuCl3. Sonicate the resulting mixture for 2 h, then add 325 mg of carbon black (Cabot, BP2000, its weight being 4 times the total metal weight of the precursors RhCl3 and RuCl3), and stir to disperse for 18 h to ensure uniform dispersion. Next, use a rotary evaporator at 80 °C and 8 × 10⁻⁶ °C. 3 The mixture was dried at Pa to collect the powder sample.
[0035] b. The dried powder was placed in an H2 / Ar (5% H2) atmosphere and reduced at 900℃ for 2 hours with a heating rate of 5℃ / min to obtain a ruthenium-rhodium alloy (RhRu3 / C) supported on a carbon support.
[0036] c. Anneal the RhRu3 / C sample in air at 450℃ for 3 hours, with a heating rate of 5℃ / min. The carbon support will be oxidized into CO2 in the oxidizing atmosphere and leave, resulting in a supportless ruthenium-rhodium binary alloy oxide.
[0037] d. Finally, take 50 mg of the sample, place it in 20 mL of 1 M HCl solution and acid wash for 12 h, then centrifuge. After centrifugation, wash three times with deionized water. Finally, dry the sample in an oven at 60 °C overnight to obtain RhRu3O. x catalyst.
[0038] Example 2
[0039] In this embodiment, the binary metal oxide MRu3O formed by other platinum group elements and Ru is prepared according to the following steps. x Nanoparticles:
[0040] a. Add 0.2 mmol MCl x (M = Ir, Pd, Pt) was added to 20 mL of HCl solution (mass concentration 36.0–38.0%) and dissolved until transparent. Then, 130 mL of deionized water (DIW) and 0.6 mmol of RuCl3 were added. The resulting mixture was sonicated for 2 h, and carbon black (Cabot, BP2000, weighing 4 times the total metal weight in the precursor) was added. The mixture was stirred and dispersed for 18 h to ensure uniform dispersion. Next, a rotary evaporator was used at 80 °C and 8 × 10⁻⁶ °C. 3 The mixture was dried at Pa to collect the powder sample.
[0041] b. The dried powder was placed in an H2 / Ar (5% H2) atmosphere and reduced at 900℃ for 2 hours with a heating rate of 5℃ / min to obtain a ruthenium-based alloy (MRu3 / C) supported on a carbon support.
[0042] c. Anneal the MRu3 / C sample in air at 450℃ for 3 hours, with a heating rate of 5℃ / min. The carbon support will be oxidized into CO2 in the oxidizing atmosphere and leave, resulting in a supportless ruthenium-based binary alloy oxide.
[0043] d. Finally, take 50 mg of sample, place it in 20 mL of 1 M HCl solution and acid wash for 12 h, then centrifuge. After centrifugation, wash three times with deionized water. Finally, dry the sample in an oven at 60 °C overnight to obtain MRu3O. x catalyst.
[0044] Example 3
[0045] In this embodiment, RhRu3O, used as an anode catalyst for a PEM electrolyzer, was prepared according to the following steps. x Nanoparticles:
[0046] a. Add 0.6 mmol RhCl3 to 20 mL of HCl solution (mass concentration 36.0–38.0%) and dissolve until transparent. Then add 130 mL of deionized water (DIW) and 0.6 mmol RhCl3. Sonicate the resulting mixture for 2 h, then add carbon black (Cabot, BP2000, weight 4 times the total metal weight in the precursor) and stir to disperse for 18 h to ensure uniform dispersion. Next, use a rotary evaporator at 80 °C and 8 × 10⁻⁶ °C. 3 The mixture was dried at Pa to collect the powder sample.
[0047] b. The dried powder was placed in an H2 / Ar (5% H2) atmosphere and reduced at 900℃ for 2 hours with a heating rate of 5℃ / min to obtain a ruthenium-rhodium alloy (RhRu / C) supported on a carbon support.
[0048] c. Anneal the RhRu / C sample in air at 450℃ for 3 hours, with a heating rate of 5℃ / min. The carbon support will be oxidized into CO2 in the oxidizing atmosphere and leave, resulting in a supportless ruthenium-rhodium binary alloy oxide.
[0049] d. Finally, take 50 mg of the sample, place it in 20 mL of 1 M HCl solution and acid wash for 12 h, then centrifuge. After centrifugation, wash three times with deionized water. Finally, dry the sample in an oven at 60 °C overnight to obtain RhRuO. x catalyst.
[0050] Comparative Example 1
[0051] This comparative example provides the following two comparison samples:
[0052] Hom-RuO2 (self-made RuO2) is a sample with only RuCl3 as the precursor salt. Its preparation method is the same as in Example 1, except that the amount of RhCl3 added in step a is 0.
[0053] Com-RuO2 is a commercial RuO2 sample.
[0054] Figure 2 The images show transmission electron microscopy (TEM) and high-angle annular dark-field scanning transmission (HAADF-STEM) images of the RhRu3 / C nanoparticles prepared in Example 1 of this invention. As can be seen from the images, the alloy nanoparticles are uniformly dispersed on the carbon substrate.
[0055] Figure 3 RhRu3O prepared in Example 1 of this invention x Transmission electron microscopy (TEM) and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images of the nanoparticles. The images show that after annealing in an oxidizing atmosphere, RhRu3O... x The nanoparticles maintained a uniform and small size.
[0056] Figure 4 RhRu3O prepared in Example 1 of this invention x The elemental distribution of the nanoparticles is shown in the scanning transmission electron microscopy (STEM) mapping. The image reveals a uniform elemental distribution within the RhRu3Ox nanoparticles.
[0057] Figure 5 RhRu3O prepared in Example 1 of this invention x X-ray diffraction (XRD) patterns of the nanoparticles and the control sample. The figures show that RhRu3O x The X-ray diffraction pattern of Hom-RuO2 matches that of pure RuO2 (PDF#43-1027) and RhO2 (PDF#21-1315), and no phase separation occurs in the alloy oxide.
[0058] Electrochemical tests were performed using a standard three-electrode configuration connected to a potentiostat (IM6ex, ZAHNER elektrik) in an O2-saturated 0.1M HClO4 (pH≈1) electrolyte. Pt foil (Pt 210, Tianjin Aida) and Hg / Hg2SO4 (MMS, Tianjin Aida) were used as the counter and reference electrodes, respectively. A typical procedure involved adding 5 mg of catalyst to 1 mL of isopropanol and 20 μL of Nafion solution (5 wt%) and ultrasonically dispersing for 1 hour to produce a homogeneous catalyst slurry. Before electrode preparation, the Au electrode (0.19625 cm²) was cleaned using a plasma cleaner (Harrick PDC-002) at 740 V DC, 40 mA DC, and 29.6 W. 2 (Tianjin Aida) Surface for 2 min. After cleaning, 16 μL of catalyst slurry was dropped onto the Au electrode in four portions, and vacuum dried at room temperature after each drop (catalyst loading: 0.4 mg cm⁻¹). -2 The prepared Au electrode was assembled with the RDE assembly (Pine Instruments) as the working electrode, with a rotational speed of 2,500 rpm. For OER experiments, the recording scan rate was 10 mV s within the RHE potential range of 1.1–1.8 V. -1 LSV testing. All potentials were measured on the MMS reference electrode and converted to the reversible hydrogen electrode (RHE) scale according to E(vs RHE) = E(vs MMS) + 0.645 + 0.0591 × pH.
[0059] Figure 6 RhRu3O prepared in Example 1 of this invention x Linear sweep voltammetry (LSV) curves of binary metal oxides formed by nanoparticles and other platinum group elements with Ru in 0.1 M HClO4. The figure shows that RhRu3O x Reaching 10 mAcm -2 The overpotential is 184 mV, lower than that of Hom-RuO2 (208 mV), Com-RuO2 (253 mV), and other platinum group elements. RhRu3O... x At 10mAcm -2 The overpotential was also lower than that of RhRuO with an elemental ratio of 1:1 obtained in Example 3. x The overpotential (189mV) indicates that RhRu3O x It exhibits optimal oxygen evolution reaction kinetics.
[0060] Figure 7 RhRu3O prepared in Example 1 of this invention xX-ray photoelectron spectroscopy (XPS) spectra of the nanoparticles and the control sample in the 3d orbitals of Ru. The figures show that, relative to Hom-RuO2 and Com-RuO2, RhRu3O... x Ru 4+ 3D 3 / 2 and 3D 5 / 2 The binding energy of RhRu3O showed a negative shift, indicating that... x The surface Ru has the lowest oxidation state, and this change in electronic structure may be the reason why it exhibits the best electrochemical activity.
[0061] Figure 8 To improve the RhRu3O prepared in this invention x A schematic diagram of the PEM-WE device used for actual production evaluation of nanoparticles. The specific assembly method is as follows: Stack the following components in sequence: cathode fluid field, carbon paper, gasket, membrane electrode, gasket, platinum-plated titanium felt, and anode fluid field. Then, insert bolts into the holes of the device, ensuring the stack does not experience shear misalignment, and tighten the bolts. Use a torque wrench to tighten the eight bolts of the clamp diagonally. First, tighten the eight bolts with a torque of 2 N·m, then increase by 1 N·m each time, finally increasing to 5 N·m to complete the fixation. Next, connect the cathode (I-) and anode (I+) current leads (i.e., load cables) of the electrolyzer to the negative and positive terminals of the battery, respectively. Then, connect the cathode voltage (V-) and full-cell anode voltage (V+) induction cables of the electrolyzer to the negative and positive terminals of the battery, respectively.
[0062] The RhRu3O prepared in this invention x The material is used as the anode in a PEM-WE device for hydrogen production via water electrolysis, and the steps are as follows:
[0063] a. In a solvent with an isopropanol to water volume ratio of 1:1, the catalyst is uniformly mixed with an ionomer (5 wt% naphthol solution) comprising 40 wt% of the catalyst. On a Teflon high-temperature fabric, a 3 mg cm⁻¹ layer is formed at 40°C using a vacuum adsorption air brush method. -2 Anode catalyst layer and 0.6 mg cm -2 Pt / C cathode catalyst layer. Then, the two catalyst layers were hot-pressed and transferred to a 2*2 cm substrate at 135℃, 11T, and 5min. 2 The blank film electrode (Nafion 115) on both sides.
[0064] b. The electrolyte used is 18MΩ deionized water at a flow rate of 100 ml / min. The cathode carrier gas is N2 at a flow rate of 40 ml / min. Under room temperature and ambient pressure, the cathode operates at 50-2200 mA / cm². -2IV curves were measured in scanning current mode. Stability tests were conducted at room temperature and ambient pressure at 200 mA / cm². -2 Performed in constant current mode.
[0065] Figure 9 RhRu3O prepared in Example 1 of this invention x Activity test graphs of nanoparticles and control samples in PEM-WE devices at room temperature. The graphs show that, at the same current density, RhRu3O... x The required cell pressure is much lower than that of Com-RuO2 and Hom-RuO2, to achieve 1 Acm. -2 For example, Com-RuO2 requires a cell voltage of 2.15V, Hom-RuO2 requires 2.36V, while RhRu3O... x Only 1.90V is required.
[0066] Figure 10 RhRu3O prepared in Example 1 of this invention x Stability test results of nanoparticles in PEM-WE devices at room temperature. The figure shows that the sample exhibits stability at room temperature with a stability of 200 mA / cm². -2 Its current density has been stable for more than 1,000 hours, demonstrating its value in actual production.
[0067] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a rhodium-ruthenium binary metal oxide for use as an anode in a PEM electrolytic cell, characterized in that, Includes the following steps: a. Add RhCl3 to hydrochloric acid and dissolve until transparent. Then add deionized water and RuCl3. After ultrasonic treatment of the resulting mixture, add carbon black and stir until evenly dispersed. Dry and collect the powder sample. The molar ratio of RhCl3 to RuCl3 is 1:3, and the weight of carbon black is 2-6 times the total metal weight of RhCl3 and RuCl3. b. The dried powder was placed in an H2 / Ar atmosphere for reduction to obtain a ruthenium-rhodium alloy RhRu3 / C supported on a carbon support; c. Anneal the RhRu3 / C sample in air to oxidize the carbon support into CO2 and remove it, thus obtaining a supportless ruthenium-rhodium binary metal oxide. d. The carrier-free ruthenium-rhodium binary metal oxide sample is acid-washed in HCl solution, then washed with deionized water and dried to obtain RhRu3O for use as the anode in a PEM electrolytic cell. x catalyst.
2. The preparation method according to claim 1, characterized in that, In step a, the drying is performed using a rotary evaporator at 50-90°C and 6-9 × 10⁻⁶ °C. 3 Drying is carried out at Pa.
3. The preparation method according to claim 1, characterized in that, In step b, the reduction is carried out at 800-1000℃ for 1.5-3 hours.
4. The preparation method according to claim 1, characterized in that, In step c, the annealing temperature is 350-550℃ and the annealing time is 2-4 hours.
5. The preparation method according to claim 1, characterized in that, In step d, the concentration of the HCl solution is 0.5-2 M, the ratio of sample to HCl solution is 30-60 mg: 10-30 mL, and the acid washing time is 10-15 h.
6. A RhRu3O anode for a PEM electrolytic cell prepared by the preparation method according to any one of claims 1 to 5. x catalyst.
7. A method using the RhRu3O as described in claim 6 x The catalyst is the anode of the PEM electrolyzer.
Citation Information
Patent Citations
Preparation method and application of iridium-modified ruthenium-based transition metal doped oxide catalyst
CN117026271A
